The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.3390/md13041798
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Proteomic Analyses Reveal that Unsaturated Guluronate Oligosaccharide Modulates Multiple Functional Pathways in Murine Macrophage RAW264.7 Cells

Abstract: Alginate is a natural polysaccharide extracted from various species of marine brown algae. Alginate-derived guluronate oligosaccharide (GOS) obtained by enzymatic depolymerization has various pharmacological functions. Previous studies have demonstrated that GOS can trigger the production of inducible nitric oxide synthase (iNOS)/nitric oxide (NO), reactive oxygen species (ROS) and tumor necrosis factor (TNF)-α by macrophages and that it is involved in the nuclear factor (NF)-κB and mitogen-activated protein (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 60 publications
0
15
0
Order By: Relevance
“…Alginate is a natural polysaccharide derived from various kinds of marine brown algae. Previous studies demonstrated that AdO exhibits notably diverse pharmacological activities [ 15 , 16 , 18 , 19 ]. However, to the best of our knowledge, this is the first work to explore the effect of AdO on microglia-mediated inflammatory responses and microglial phagocytosis of Aβ.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alginate is a natural polysaccharide derived from various kinds of marine brown algae. Previous studies demonstrated that AdO exhibits notably diverse pharmacological activities [ 15 , 16 , 18 , 19 ]. However, to the best of our knowledge, this is the first work to explore the effect of AdO on microglia-mediated inflammatory responses and microglial phagocytosis of Aβ.…”
Section: Discussionmentioning
confidence: 99%
“…Alginate-derived oligosaccharide (AdO) produced by depolymerizing the polysaccharide using various degradation methods shows a variety of biological activities. Unsaturated AdO depolymerized by enzymatic depolymerization exerts anti-tumor [ 15 ], anti-oxidant [ 16 , 17 ], and immunomodulatory effects [ 18 , 19 ], whereas the saturated AdO prepared by acid hydrolysis posses low bioactivities. The anti-inflammatory activities of alginate have been described [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The spots showing significant differences in specific carbonylation levels between autism and control using Student’s t test statistical analysis ( p  < 0.05) were chosen for identification. For protein identification, the spots of interest were excised manually from the silver-stained gels and tryptic in-gel digestion was performed as described previously [22]. Mass spectroscopy analysis was performed on a 5800 MALDI TOF/TOF mass spectrometer (AB Sciex, Foster City, CA, USA) [21, 22] or Triple TOF 5600 system (AB Sciex) [23].…”
Section: Methodsmentioning
confidence: 99%
“…In addition to signaling pathway activation, pathways involved in antioxidant activity, glycolysis, cytoskeletal processes, and translational elongation were also regulated by enzymatically produced GAOS. Comparative proteomic analysis coupled with two‐dimensional electrophoresis, MALDI‐TOF/TOF‐MS, and Western blot supported the regulation of these pathways (Xu et al., ). Elucidation of structure–function relationship on AOS immunomodulatory activity would help to introduce the targeted production of AOS with desirable composition and structure features thus favorable for their utilization as natural immunomodulators in food products.…”
Section: Health Beneficial Effects and Potential Aos Applicationsmentioning
confidence: 96%